2018
DOI: 10.21873/invivo.11363
|View full text |Cite
|
Sign up to set email alerts
|

Peak of Standardized Uptake Value in Oral Cancer Predicts Survival Adjusting for Pathological Stage

Abstract: A higher p-SUVpeak on pretreatment F-FDG-PET/CT is a prognostic parameter of identifying lower survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…All these, in addition to the immune-responsiveness studied here, are contributors to differential susceptibility of individual patients. These markers can potentially be correlated with information from the systemic recordings found in clinicopathological databases of the oral cancer patients for the prediction of prognosis outcomes, such as survival (30) and metastasis (31). Additional genotype-phenotype correlation studies can help in revealing the biological meanings of these genomic markers, extending our understanding of the etiology of each oral cancer patient, leading to personalized therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…All these, in addition to the immune-responsiveness studied here, are contributors to differential susceptibility of individual patients. These markers can potentially be correlated with information from the systemic recordings found in clinicopathological databases of the oral cancer patients for the prediction of prognosis outcomes, such as survival (30) and metastasis (31). Additional genotype-phenotype correlation studies can help in revealing the biological meanings of these genomic markers, extending our understanding of the etiology of each oral cancer patient, leading to personalized therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…11 A high SUVpeak in early-stage cervical cancer can reflect more aggressive lesions, can help predict prognosis, 27 and is a prognostic parameter of poor survival outcomes in patients with oral cancer. 28…”
Section: Discussionmentioning
confidence: 99%
“…11 A high SUVpeak in early-stage cervical cancer can reflect more aggressive lesions, can help predict prognosis, 27 and is a prognostic parameter of poor survival outcomes in patients with oral cancer. 28 Berg et al 9 showed that SUVmax and SUVmean were significantly lower in patients with CAH compared to those with grade 1 endometrial carcinoma (EECG1; P < .01), with AUCs of 0.87 and 0.97, respectively. By contrast, MTV did not significantly differ between CAH and EECG1 (P ¼ .1).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of subgroup or protocol, all these studies found that high levels of SUV before surgery or follow-up predicted adverse outcomes for patients with OSCC. Using the same tool, eight studies evaluated MTV and TLG alone or in combination with SUVmax ( 24 , 25 , 30 , 34 38 ), and some found that both MTV and TLG might be prognostic for the survival of patients with oral cancer.…”
Section: Resultsmentioning
confidence: 99%
“…For meta-analysis we included the data of 8 combined studies ( 25 , 27 , 29 , 31 , 33 , 34 , 37 , 38 ). The high SUVmax parameter was related to worse OS in OSCC (pooled HR=4.042, 95%CI: 2.573-6.348, z-value=6.063, P=0.000) ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%